STUDENTS’ LISTENING COMPREHENSION OF COMMERCIAL ADVERTISING VIDEOS AT SMK TAMANSISWA 1 PALEMBANG - Samaya, Doni; Noor Amalia, Falina; Nurulanningsih; Elvinna Manurung, Jenny (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
Studying advertising text is one of the skills that should be mastered by SMK students. It is stated in the 2013 (K13) curriculum for class XII in the odd semester based on core competencies 3 and 4. Hence, this paper describes the students' skills in listening comprehension on video advertisements and determines the level of students' skill categories based on the assessment standards that apply in the research field. The research method uses a quantitative descriptive method. The sample involved 28 students of class XII OTKP 1, which consisted of 20 female and 8 male students. The data collection technique was carried out by using a short description test after listening to and transcribing the advertising videos into written form. The data analysis technique was based on the comprehensive listening assessment rubric, which was adapted and modified by Nurgiyantoro in 2011. The results data of a short essay based on the students’ listening comprehension results are described and concluded. Based on the results of the research and discussion, it implies that 1) the research sample is considered to be ingenious in listening to commercial advertisement videos and 2) the average value of the research sample is 74.2 or is categorized to achieve the objectives based on the Minimum Completeness Criteria (KKM) at SMK Tamansiswa 1 Palembang. Thus, it can be concluded that SMK Tamansiswa 1 Palembang student is skilled in listening to commercial advertisement videos, in which twenty-five students achieve scores with the category achieved goals.